2013
DOI: 10.1089/ped.2013.0226
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Asthma Knowledge, Aptitude, and Practice in High Healthcare Utilizing Children: Effect of an Educational Intervention

Abstract: Factors underlying high healthcare utilization among Hispanic and African American (AA) children with asthma are not well known. We hypothesized that low parental knowledge and suboptimal practices are associated with high healthcare utlization and sought to elucidate these factors and identify ethnicity-specific differences. We also hypothesized that a targeted educational intervention will decrease emergency department (ED) visits and hospitalizations. A 57-item questionnaire investigating asthma knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
22
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 31 publications
11
22
1
1
Order By: Relevance
“…Parents, including parents of ethnic minorities [43] need guidance to interpret information, and translate it into knowledge in order to facilitate their judgment about the severity of their child's disease in order to support the child to act in accordance to need [19,44]. Another contributing factor to medical non-adherence is parental motivation and their belief in their child's asthma medication [4].…”
Section: Societal Perspective: Role Of Peersmentioning
confidence: 99%
“…Parents, including parents of ethnic minorities [43] need guidance to interpret information, and translate it into knowledge in order to facilitate their judgment about the severity of their child's disease in order to support the child to act in accordance to need [19,44]. Another contributing factor to medical non-adherence is parental motivation and their belief in their child's asthma medication [4].…”
Section: Societal Perspective: Role Of Peersmentioning
confidence: 99%
“…Reported depression and anxiety is high among caregivers of children with asthma (Silver, Warman, & Stein, 2005; Szabo, Mezei, Kovari, & Cserhati, 2010), and is associated with higher number of unscheduled health care visits (Spurrier NJ et al, 2003). While some of these factors are typical to residence in urban inner-city neighborhoods and do not differ between Hispanics/Latinos and African Americans (Rastogi D, Madhok N, & Kipperman S, 2013), others including language barrier (Mosnaim GS et al, 2007), influence the quality of care provided to Hispanic/Latino families. However, several intervention studies have demonstrated improvement in adherence with appropriate education and follow-up (Rastogi D et al, 2013; Spiegel J et al, 2006).…”
Section: Childhood Asthmamentioning
confidence: 99%
“…Education has a primary role in asthma management and the role of education has been assesed in asthma control in previous studies [13][14][15][16][17][18] . Asthma education programs in these studies are different in their nature by means of population, intervention and duration.…”
Section: Volume 58 • Number 4 Education Intervention In Uncontrolled mentioning
confidence: 99%
“…Education of caregivers help their control of home environment and their childrens'asthma signs and symptoms 17 . Asthmatic children whose caregivers underwent a targeted education were found to have fewer emergency department visits 15 . But there is also a study in the literature that indicates educational intervention is not beneficial when targeted to only caregivers 14 .…”
Section: Volume 58 • Number 4 Education Intervention In Uncontrolled mentioning
confidence: 99%
See 1 more Smart Citation